Country-of-origin misclassification awareness and consumers' behavioral intentions: Moderating roles of consumer affinity, animosity, and product knowledge. Issue 3 (8th May 2017) - Cakici, N. Meltem; Shukla, Paurav
Abstract : Purpose: Extant research shows that consumers regularly misclassify country-of-origin (COO) associated with brands. The purpose of this paper is to examine changes in behavioral intentions (i.e. purchase intentions for self and others and brand judgments) when consumers are made aware that they have misclassified the COO and then are informed of the brand's correct origin. Drawing on cognitive dissonance theory, the authors also explore the moderating roles of consumer affinity, animosity, and product knowledge. Design/methodology/approach: Two experiments test the direct and moderating effects of COO misclassification awareness on behavioral intentions. Findings: The findings show detrimental effects of misclassification on behavioral intentions when consumers have high affinity with misclassified COO. Moreover, the experiments demonstrate a significantly greater decrease in behavioral intentions among experts than novices in the low-affinity condition and the reverse effect in the high-affinity condition. Practical implications: The negative effects of COO misclassification on consumer behavioral intentions highlight the need for managers to proactively avoid misclassification. The findings should also aid managers in developing responsive marketing campaigns that consider consumer affinity, animosity, and level of product knowledge. Originality/value: This research is the first to compare consumer behavioral responses before and after COO misclassification awareness. The study demonstrates that cognitive dissonance underpins the process of misclassification. It also contributes to COO literature by examining the interaction of consumer affinity and animosity with product knowledge and their influence on consumer behavior in the case of COO misclassification.